Evaluation for particles capturing in magnetic separation using magnetic particles movement simulation (Effects of number of magnets, magnet arrangements, and magnetic coercive force) - Toru INABA; Shinya MATSUOKA; Yoshihiro YAMASHITA; Taku SAKAZUME (Nihon Kikai Gakkai ronbunshu, 2014)
An analysis program of predicting the movement of magnetic particles in flow, gravity, and magnetic fields was applied for magnetic separation process in a small vessel of an in-vitro diagnostic system. This program evaluates not only the drag, gravity, and magnetic force in a flow field but also the friction force between a particle and a wall. The friction force was simply modeled as static and dynamic friction forces. The coefficients of the static and dynamic friction forces were determined by comparing simulated and measured magnetic particles capturing distributions. Using this program, we evaluated capturing time and distribution on the wall of the vessel by changing number of magnets, magnet arrangements, and magnetic coercive forces. Capturing distribution of the magnetic particles depends on number of magnets and magnet arrangement, and becomes specific pattern according to the magnetic field generated by magnets. Number of magnets and magnet arrangement can also change capturing time. Especially, magnet arrangement with alternate magnetic pole becomes more uniform distribution and shortens capturing time. Magnet arrangement with stronger magnetic coercive force makes the capturing time short. This simulation method for solving multi physics problems is very effective at predicting the movements of magnetic particles and is an excellent tool for the development and design of devices.